PENGARUH GAYA HIDUP SERTA LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF GENERASI Z PADA MASA PANDEMI - Tiana Fungky; Tiara Puspita Sari; Vicky F Sanjaya (LP2M Universitas Bina Bangsa, 2022)
The study aims to test the influence of lifestyle and financial literacy on the consumptive behavior of generation Z during pandemic times. The method used in this study is by distributing questionnaires to Sharia Business Management students, UIN Raden Intan Lampung class of 2019. The number of researchers was 53 sempel. All hypotheses proposed are positively influential lifestyles with original sample values (0.747) and significant to the consumptive behavior of generation Z with P-values (0,000 < 0.05 represented by activity indicators, and opinions. Showing that the higher the lifestyle, the higher the consumption behavior of generation Z. As a student of Islamic business management should be able to pay attention again about the knowledge of financial literacy knowledge because good financial literacy knowledge will save students from consumptive behavior. Because the results showed that financial literacy had a negative and significant effect on the original value of the sample (-0.316) and significant to the consumptive behavior of generation Z with p-values (0.036 < 0.05) represented by indicators of basic knowledge about personal finance, insurance, and investment. Showing that the higher the level of knowledge of financial literacy, the lower the consumptive behavior of Generation Z